A tendency to worse course of multisystem inflammatory syndrome in children with obesity: MultiOrgan Inflammatory Syndromes COVID-19 related study - Gawlik, Aneta Monika; Berdej-Szczot, Elżbieta; Chmiel, Iga; Lorek, Miłosz; Antosz, Aleksandra; Firek-Pędras, Małgorzata; Szydłowski, Lesław; Ludwikowska, Kamila Maria; Okarska-Napierała, Magdalena; Dudek, Natalia; Piwoński, Krzysztof; Afelt, Aneta; et al. (Frontiers in Endocrinology, 2022)
Background A new disease entity called multisystem inflammatory syndrome in children (MIS-C) is a rare consequence of COVID-19 infection. The pathophysiology and risk factors of MIS-C are still unclear, and the clinical manifestation ranges from milder forms to cases needing intensive care unit treatment. Based on available data, obesity is linked to pro-inflammatory stimulation. Moreover, several studies showed that obesity could play a role in COVID-19 severity and its comorbidities among the adult and children’s populations. This study aimed to investigate the influence of overweightedness/obesity in childhood for the course of MIS-C in Poland. Methods This study presented data from the national MultiOrgan Inflammatory Syndromes COVID-19 Related Study (MOIS-CoR) collected between 4 March 2020 and 20 February 2021. Of the 371 patients that met the Polish MIS-C criteria, 306 were included for further analysis. Results Children who are obese (OB with body mass index (BMI) ≥95th percentile) and overweight (OV with BMI ≥85th percentile but <95th percentile) (28 and 49 patients, respectively) represented 25.1% (n=77) of all recruited patients. Complete recovery at the time of discharge presented in 93% of normal body weight (NW) participants and 90% of OV children (p>0.05). Among OB children, 76% recovered fully, which differed from the NW group (p=0.01). Calculated odds ratio (OR) of incomplete recovery for OB children was 4.2. Irrespective of body weight, there were no differences (p>0.05) in the length of hospitalization and the duration of symptoms (for OB, 13 and 16.5 days; for OV and NW, 10 and 14 days, respectively), as well as in the frequency of cardiovascular abnormalities, necessity of oxygen therapy (OB, 26.9%; OV, 23.9%; and NW, 20.7%), and intravenous immunoglobulin and glucocorticosteroid (GCS) treatment. Conclusion The higher risk of incomplete recovery and observed tendency toward a worsening course of MIS-C in patients with obesity suggest the need for further studies to confirm and understand our findings.